Faut-il ajouter une aide climatique ou mieux intégrer les préoccupations climatiques dans l’aide au développement? - Jean-Paul Ledant (VertigO)
The obligation of developed countries to support developing countries in their attempts to address climate challenges leads to question the linkage between this “climate aid” and development aid. We acknowledge that climate change creates a need for qualitative and quantitative changes in development aid benefitting to vulnerable countries and that the addition of an aid dedicated to climate issues (climate finance) partly responds to this need. However we show that this approach mainly provides inconveniences compared with an increase in development aid associated with adequate climate mainstreaming in all its components. We expect that this option would better contribute to a development decoupled from greenhouse gas emissions and adapted to climate constraints.